Speed Comparison of 30-Meter between Breaststroke and Freestyle Swimming Among Sports Science Students at Universitas Negeri Makassar - Primadi, Muhamad Baidhowi (Journal Physical Health Recreation (JPHR), 2025)
Abstract. This study aims to examine the difference in swimming speed between freestyle and breaststroke over a 30-meter distance among Sports Science students at Universitas Negeri Makassar. Freestyle is widely recognized for its biomechanical efficiency compared to breaststroke, and is therefore hypothesized to result in shorter completion times. A quantitative approach with a comparative research design was employed. The sample consisted of 22 students (17 males and 5 females) who were proficient in both swimming techniques. Time data were collected through direct stopwatch measurements and analyzed using a paired sample t-test. The analysis revealed that the mean completion time for freestyle was 27.60 seconds (SD = 7.17), whereas breaststroke recorded a mean time of 38.75 seconds (SD = 8.32). Statistical testing indicated a significant difference between the two styles (t = 7.11; p < 0.001), confirming that freestyle is significantly faster than breaststroke over a 30-meter distance. These findings provide valuable insights for the development of swimming training programs, particularly in enhancing speed and movement efficiency.Keywords: Swimming, breaststroke, freestyle, speed, student.